DESAIN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS INTEGRASI NILAI-NILAI SPIRITUAL DAN KARAKTER - Wati Wati (JIP: Jurnal Ilmu Pendidikan, 2025)
Learning is a process of interaction between students and educators and learning resources in a learning environment to acquire knowledge, master skills and habits, and form attitudes and beliefs in students. In other words, learning is a process to help students learn well. To achieve optimal learning objectives, an interesting learning design is required. An effective Islamic education learning design can help students understand religious values and apply them in their daily lives. This study aims to analyse the effectiveness of an Islamic education learning design based on the integration of spiritual values and character. This study uses a qualitative approach and a literature review. The results show that this learning design can improve students' understanding of religious values and shape good character in students.